Analyzing Stock Volatility in Nepse Index: A Comparative Study between Symmetric and Asymmetric GARCH Models - Dahal, Dipak Kumar; Gautam, Bidur; Gnawali, Bindu (Journal of Multidisciplinary Research Advancements, 2026)
The stock exchange of each country is the barometer of its economy and plays a vital role in the efficient allocation of scarce financial resources. However, the stock exchange faces conditions of uncertainty and unpredictability, which exhibit volatility. Such characteristics of the stock exchange undesirably affect the financial market. This study examined the volatility pattern of the Nepal Stock Exchange (NEPSE) using the daily return series of the NEPSE index from August 15, 2014, to April 30, 2024. A total of 2218 values were considered for the study. For the study, the ARIMA (1,1,3) model was considered to determine the mean equation, GARCH (1,1) for measuring the conditional volatility, GARCH-M (1,1) for the risk premium, and TGARCH (1,1), EGARCH (1,1), and PGARCH (1,1) to determine the presence of leverage effects on the stock exchange. It was concluded that the Nepalese stock exchange is volatile, exhibiting volatility clustering, indicating that volatility is large, followed by even larger volatility. Additionally, it exhibits both symmetric and asymmetric effects on volatility. GARCH (1,1) and GARCH-M (1,1) models exhibit a symmetric effect, in which the impact of positive and negative shocks on returns is equal. The GARCH-M (1,1) model indicates that the Nepalese stock market does not provide additional returns to investors for taking risks. On the other hand, the TGARCH (1,1), EGARCH (1,1), and PGARCH (1,1) models reveal an asymmetric effect: the negative effect of a shock on returns is larger than the positive effect. The study concludes that the PGARCH (1,1) model best captures the volatility persistence of the daily return series of the NEPSE index.